The Impact of Government Expenditure on Economic Growth and Inflation Rate in Nigeria - Ayinde, Musa Adeyemi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
The research’s objective is to investigate the influence of government recurrent expenditure and government capital expenditure on economic growth; the impact of government recurrent expenditure and government capital expenditure on the inflation rate; how well the government expenditures work hand-in-hand with the money supply in influencing economic growth and inflations rate; and the long-run relationship between inflation rate and economic growth. All in the case study of Nigeria, from 1981 to 2022. With the use of the ARDL Bound Test approach, there exists a long-run relationship between the variables. The estimated ARDL long-run coefficients showed that government recurrent expenditure and money supply have a positive relationship with economic growth and inflation rate; government capital expenditure has a negative relationship with economic growth and inflation rate; and a negative relationship between inflation rate and economic growth. According to the Granger Causality Test results, there is a unidirectional causality from government expenditures to economic growth and money supply. However, no directional causality between government expenditures and inflation rate; inflation rate and economic growth; and money supply and inflation rate.

ÖZ: Araştırmanın amacı, hükümet`n car` ve sermaye harcamalarının, ekonom`k büyüme ve enflasyon üzer`ndek` etk`s`n` araştırmaktadır. Ekonom`k büyümey` ve enflasyon oranını etk`lemede, hükümet`n car` harcamaları ve sermaye harcamalarının, para arzı `le el ele ne kadar `y` çalıştığını, ekonom`k büyüme ve enflasyonun uzun dönem `l`şk`s`n` ele alarak göstermey` amaçlamıştır. Söz konusu `nceleme N`jerya `ç`n yapılmış olup, 1981 yılından 2022’e kadar olan sürey` kapsamaktadır. ARDL Sınır Test` Yaklaşımı sonuçlarına göre değ`şkenler arasında uzun dönem `l`şk` bulunmaktadır. Tahm`n ed`len ARDL uzun dönem katsayıları, hükümet`n car` harcamaları ve para arzının, ekonom`k büyüme ve enflasyon oranı `le poz`t`f b`r `l`şk`ye sah`p olduğunu göster`rken; hükümet`n sermaye harcamalarının ekonom`k büyüme ve enflasyon oranı üzer`nde negat`f etk`s` olduğu dolayısıyla ekonom`k büyüme ve enflasyon oranı arasında da negat`f `l`şk` olduğu sonucunu gösterm`şt`r. Granger Nedensell`k Test sonuçlarına göre, kamu harcamalarından ekonom`k büyümeye ve para arzına doğru tek yönlü nedensell`k vardır. Ancak, kamu harcamaları ve enflasyon, ekonom`k büyüme ve enflasyon, para arzı ve enflasyon arasında yönlü b`r nedensell`k bulunmamaktadır.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2024. Supervisor: Prof. Dr. Hasan Güngör
Keywords: Government Expenditure--Inflation Rate--Economic Growth--Nigeria; Economic Conditions and Development--Nigeria; Public expenditures--Public finance; Government spending policy; Government recurrent expenditure, government capital expenditure